Parent–Child Relationships and Academic Performance of College Students: Chain-Mediating Roles of Gratitude and Psychological Capital - Li, Jun; Huang, Jianhao; Hu, Ziao; Zhao, Xiang (Frontiers in Psychology, 2022)
This study used the Social Cognitive Theory and Broaden-and-Build Theory to propose and validate a chain mediation model. In total, 417 Chinese college students were studied to explore the effects of parent-child relationships on their academic performance. In addition, we investigated the chain-mediating roles of gratitude and psychological capital. The results showed that (1) the parent-child relationship significantly and positively affected the academic performance of college students; (2) gratitude partially mediated the parent-child relationship and the academic performance of college students; (3) psychological capital partially mediated the parent-child relationship and the academic performance of college students; and (4) gratitude and psychological capital exerted a chain-mediating effect between parent-child relationships and the academic performance of college students. Based on the results of the study, we conclude that the parent-child relationship not only directly affects the academic performance of college students but also indirectly affects it through the chain mediation of gratitude and psychological capital. Moreover, we proposed reasonable suggestions on how colleges and universities can guide students to deal with parent-child relationships, strengthen gratitude education, and improve psychological capital.